Counseling and Education of Hand Washing and How to Wearing a Good and Correct Mask in MI Cikananga - Asman Sadino; Elsa Novita Ismawati; Faisal Ashidiky; Intan Maharani4; Mochamad Ridho Firdaus; Salsa Silviani; Wahyu Romadon (Fakultas Kewirausahaan Universitas Garut, 2021)
ABSTRACK The increase from day to day in the number of patients infected with the Covid-19 virus is difficult to control, which must be anticipated by urging the public, especially early childhood, to adopt a new healthy lifestyle according to health protocols during the Corona virus pandemic. This counseling aims to provide knowledge and the ability to apply clean and healthy living behavior (PHBS) to students at MI Cikananga Banyuresmi Village in anticipating the prevention of the spread of COVID-19 through good and correct procedures for washing hands, wearing, removing and disposing of masks. The results obtained from this activity are to increase understanding of the importance of clean and healthy living behavior (PHBS) in efforts to prevent COVID-19 through the procedures for washing hands, wearing, removing and disposing of masks that are good and truly at the individual, family and environmental levels. This socialization is useful for raising students' awareness of the importance of implementing PHBS in the pandemic era. ABSTRAK Peningkatan dari hari kehari jumlah pasien yang terinfeksi virus Covid – 19 sulit untukdi kendalikan, yang harus di antisipasi dengan menghimbau masyarakat terutama pada anak usia sejak dini untuk melakukan pola hidup sehat baru sesuai protokol kesehatan semasa pandemic Corona virus ini. Penyuluhan ini bertujuan untuk memberikan pengetahuan dan kemampuan untuk menerapkan perilaku hidup bersih dan sehat (PHBS) terhadap siswa MI Cikananga Desa Banyuresmi dalam mengantisipasi pencegahan penyebaran COVID-19 melalui tata cara mencuci tangan, memakai, melepas dan membuang masker yang baik dan benar. Hasil yang diperoleh dari kegiatan ini yaitu menambah pemahaman siswa terhadap pentingnya perilaku hidup bersih dan sehat (PHBS) dalam upaya pencegahan COVID – 19 melalui tata cara mencuci tangan, memakai, melepas dan membuang masker yang baik dan benar ditingkat individu, keluarga dan lingkungan. Sosialisasi ini bermanfaat untuk menumbuhkan kesadaran siswa akan pentingnya penerapan PHBS di era pandemi.